Pengaruh Disiplin Kerja, Stres Kerja, Dan Lingkungan Kerja Terhadap Kinerja Karyawan: Studi Kasus Pada PT Kebon Agung Pabrik Gula Unit Trangkil Pati - Aprilia, Putri Dewi; Sijabat, Rauly; Darmaputra, M. Fadjar (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2024)
This research aims to determine the influence of work discipline, work stress, and work motivation on employee performance at PT Kebon Agung Sugar Factory, Trangkil Pati unit. This research uses quantitative research methods that use statistical analysis. The population in the research was 100 employees and the sample determined in this research was 100 employees using a saturated sampling technique. This research uses SPSS software to answer the main facts using a list of questionnaires that have been answered by respondents. The findings in this research are that work discipline influences employee performance, work stress influences employee performance, and the work environment influences employee performance at PT Kebon Agung Sugar Factory, Trangkil Pati unit.